Renal denervation in patients who do not respond to cardiac resynchronization therapy - Pietilä-Effati Päivi; Höglund Mathias; Käräjämäki Aki; Höglund Filip; Nabb Anne-Maria; Matila Eija; Koistinen Juhani M (Informa Healthcare, 2025)
Cardiac resynchronization therapy (CRT) reduces the morbidity and mortality in advanced heart failure (HF) in about two-thirds of the patients. Approximately one-third of the patients do not respond to CRT. The overactivity of sympathetic nervous system is associated with advanced HF and deteriorates the hemodynamic state. We tested the hypothesis that controlling sympathetic overactivity by renal denervation (RDN) could be beneficial in nonresponders for CRT. In our HeartF-RDN study (ClinalTrials.gov. NCT02638324), RDN could not reverse the progression of HF in subjects with New York Heart Association Classification (NYHA) III-IV stage symptoms.